PENINGKATAN TEKNIK PENGOLAHAN BUAH KELAPA MENJADI MINYAK GORENG BERMUTU (VCO) MELALUI PROSES FERMENTASI - Martini, Martini; Lindawati, S. A.; Oka, A.A.; Utami, I.A.; Kartini, A.A.S. (Buletin Udayana Mengabdi, 2012)
This community activity of natural fermentation on processing origin coconut oil (VCO) was conducted at Pengembungan I, Bongkasa village,Abiansemal district, regency of Badung, Denpasar on September 28 and 29 th 2009 .The purpose of this activity was to improve the knowledge and society skill of natural fermentation on processing VCO. The methods of activity were by giving training and councelling to farmers who merged into group of Pengembungan I Bongkase about fungsional property of VCO and technology of natural fermentation processing VCO. It can be concluded that, the participants very much like colour, viscocity and be interested in VCO